2006
DOI: 10.1080/09291010600645780
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between morningness – eveningness and final school leaving exams

Abstract: Pupils shift their time of day preferences from morningness to eveningness during the age of puberty. Therefore, early school start times may have a negative influence on school functioning, adolescent health and on grade point average. Here, we show that morningness -eveningness influences school performance as measured by the final school leaving/university entrance certificate. One hundred and thirty-two university students aged between 20 and 22 years participated in our study. We found a highly significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 34 publications
8
84
0
Order By: Relevance
“…In a study of adolescents, MT were reported to perform better on final school examination (Randler & Frech, 2006). However, the authors correctly noted that school start time is early, while adolescents biologically tend to shift towards eveningness at this time (Tonetti et al, 2008).…”
Section: Cognitive Stylesmentioning
confidence: 98%
“…In a study of adolescents, MT were reported to perform better on final school examination (Randler & Frech, 2006). However, the authors correctly noted that school start time is early, while adolescents biologically tend to shift towards eveningness at this time (Tonetti et al, 2008).…”
Section: Cognitive Stylesmentioning
confidence: 98%
“…For instance, morning-types are more conscientious and agreeable (e.g. Randler, 2008a), have higher scores in persistence and self-directedness (Adan et al, 2010), are more satisfied with their lives comparing to eveningtypes (Randler, 2008b), and have higher academic scores (Randler & Frech, 2006). Given these differences, it is not surprising that chronotypes also differ in their cognitive performances in a time of the day that matches or mismatches their chronotypes.…”
Section: The Morningness-eveningness Dimensionmentioning
confidence: 99%
“…Alternatively to arbitrary cut-offs some authors have classified participants regarding their studied samples, contrasting for instance the P 10 with P 90 (Natale & Cicogna, 2002) or Q 1 with Q 4 (Randler & Frech, 2006). Additionally, other authors have used scale-scores as reflecting a continuum (Natale & Cicogna, 2002).…”
Section: Measurement Of Morningness-eveningnessmentioning
confidence: 99%
“…In Germany, eveningtype students in high school showed significantly more use of stimulants and depressants associated with managing sleep such as coffee, cola, alcohol and nicotine when compared with morning-type students (Preckel et al 2013). In Baden-Württemberg, a study found highly significant differences in Abitur scores (used for German university entrance) with evening types having lower performance (Randler and Frech 2006). Other studies show that evening-type adolescents may have increased risk of health and mental health problems (Giannotti et al 2002;Hsu et al 2012).…”
Section: Other Educational Considerationsmentioning
confidence: 99%